A Strategy for IMF Engagement on Social Spending : Background Papers. (Policy Papers; Policy Paper ;, 2019)
This Supplement presents an account of the extensive consultations and the results of various analyses that supported the development of 'A Strategy for IMF Engagement on Social Spending.'.